2021
DOI: 10.1001/jamanetworkopen.2021.0553
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Trends in Smoking Among Surgical Patients in Michigan, 2012-2019

Abstract: IMPORTANCESurgery is a teachable moment, and smoking cessation interventions that coincide with an episode of surgical care are especially effective. Implementing these interventions at a large scale requires understanding the prevalence and characteristics of smoking among surgical patients. OBJECTIVES To describe the prevalence of smoking in a population of patients undergoing common surgical procedures and to identify any clinical or demographic characteristics associated with smoking. DESIGN, SETTING, AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…A significant proportion of patients had ASA-III, which is similar to a study which found higher odds of smoking among patients with more serious ASA physical status. 15 Most smokers in the current study were either illiterate/undergraduate (20.7%) or graduate (20.6%). This might be due to stress among specific groups related to peer pressures, social, cultural and domestic stresses, workplace stress and/or unemployment in society etc.…”
Section: Discussionmentioning
confidence: 64%
“…A significant proportion of patients had ASA-III, which is similar to a study which found higher odds of smoking among patients with more serious ASA physical status. 15 Most smokers in the current study were either illiterate/undergraduate (20.7%) or graduate (20.6%). This might be due to stress among specific groups related to peer pressures, social, cultural and domestic stresses, workplace stress and/or unemployment in society etc.…”
Section: Discussionmentioning
confidence: 64%
“…The estimates are predicated on a 23.9% smoking rate which may not accurately reflect the 2016–17 surgical patient smoking rates. However, wide uncertainty intervals (17.9%, 29.8%) are included in the probabilistic sensitivity analysis to account for this parameter uncertainty in the final estimates [ 36 ] and recent evidence suggests the assumed surgical patient smoking rate is plausible [ 31 ]. Unfortunately, recent estimates on the number of excess HBDs associated with SSIs in Australia are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking rates tend to be higher in surgical populations compared with the general population [ 31 ]. In the last 10 years, three Australian studies have reported smoking rates in orthopaedic trauma [ 26 , 27 ] and acute fracture patients [ 28 ] between 19.6% and 32.8%.…”
Section: Methodsmentioning
confidence: 99%
“…38 Multiple investigators have identified the very significant clinical benefits that follow the delivery of smoking cessation in cardiac settings. [39][40][41][42][43][44][45] Moreover, the advantages of hospital smoking cessation programmes have been clearly documented across an array of clinical disciplines: addressing smoking among surgical patients [46][47][48] ; combating peri-operative complications by anaesthesiologists 49 50 ; reducing the multiple smoking-related complications following orthopaedic procedures [51][52][53][54][55][56][57] ; demonstrating the benefits of cessation services in psychiatric settings [58][59][60] and identifying opportunities to deliver tobacco-dependence treatment in emergency departments. 61 62…”
Section: Smoking Cessation In Hospital Settingsmentioning
confidence: 99%